Customer Experience and Satisfaction in Private Insurance Web Areas - Méndez-Aparicio, M. Dolores; Jiménez-Zarco, Ana; Izquierdo-Yusta, Alicia; Blazquez-Resino, Juan Jose (Frontiers in Psychology, 2020)
Digital transformation has allowed to offer additional services - which complement the main product - both in terms of use, emotional and relationship terms. Focused on a traditionally rational insurance customer offering a value that explores the customer's emotions, from co-creating with the user, allows brand differentiation. Given this idea, this document has three purposes. First, identify the role of expectations and the perceived quality of the customer's digital experience. Secondly, to identify the relationship between experience and satisfaction gained in private insurance web areas. Third, identify the most valued digital attributes by the user. A sample of 4,178 customers registered was analyzed using the partial least squares technique. The model is highly predictive to customer experience and evidence the important relationship between the WOW effect and satisfaction, as well as the weak but doble role that expectations play on insurance digital self-service. The model demonstrates that expectations are only relevant before web consumption, because during the process it is the perceived digital quality, in particular the usefulness, information and technology, that offer a true customer experience. This article offers high academic value because it more accurately defines the determinants of the digital insurance customer experience and its effect on customer satisfaction in digital services. While expectations influence attitude before service, this research reveals that perceived digital quality is what delivers a true customer experience. Strategically, the implications are immediate in the field of business as it shows the importance of co-creation in digital design, not only because of the significant savings in implementation costs but also because it guarantees a greater experience, essential in the loyalty of its customers. This ensures the sustainable growth of the company.